Eko Sri Haryanto PENGEMBANGAN DESAIN SUVENIR MUSEUM SANGIRAN DENGAN PENDEKATAN LOKALITAS DAN TEKNIK DAUR ULANG - Eko Sri Haryanto; Tri Prasetyo Utomo (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Souvenir is one of the media used as a support for the promotion of tourism objects. Good souvenir productsin addition to increasing the economic value of the product, can also be used as a medium of imaging a touristattraction in order to attract visitors to come and make visits. This applied research aims to find out souvenirproducts from traders in the Sangiran Museum, then a new souvenir design is carried out in accordance withthe demands of the function, economy, culture and image of the Sangiran Museum attractions. Souvenirdesigns made are expected to function well in supporting the appearance of the Sangiran Museum’s distinctiveproducts, in the end it is hoped that there will be additional transactions so as to increase the sales turnover ofsouvenir sellers in the Sangiran Museum environment. The design is based on the rules of the functions ofuse, safe and economical, environmentally friendly and has a distinctive character according to tourist destinationsin the Sangiran Museum. The object of applied design research is souvenir products at the SangiranMuseum, the method used in this study is descriptive with a qualitative approach supported by quantitativedata or also called multiple research strategies. Quantitative here uses data that is the result of observationsin the field, then compared with referenced references, resource persons and analyzed based on researchers’interpretation, then the design activities begin with the product discovery stage to obtain the results of innovationin the product design process. The results of this applied research are in the form of design and souvenirmoke up in accordance with the rules; the function, economy, beauty, locality and image of the SangiranMuseum. The results of the applied research are also expected to provide enrichment of the Interior AccessoriesCourse in the Interior Design Study Program, ISI Surakarta.